On some models for cancer cell migration throughtissue networks - Jan Kelkel; Christina Surulescu (Mathematical Biosciences and Engineering)
We propose some models allowing to account for relevant processes at the various scales of cancer cell migration through tissue, ranging from the receptor dynamics on the cell surface over degradation of tissue fibers by protease and soluble ligand production towards the behavior of the entire cell population.   For a genuinely mesoscopic version of these models we also provide a result on the local existence and uniquenessof a solution for all biologically relevant space dimensions.